Economic Instability and Global Market Fluctuations in 2023: Analyzing Causes, Impacts, and Policy Responses - Sukomardojo, Tekat; Adisaputra, Ateng Kusnandar; Cakranegara, Pandu Adi; Irawati, Marsha Ayunita; Hendarto, Totok (International Journal of Science and Society, 2024)
The economic instability and global market fluctuations that will occur in 2023 have created various complex economic challenges and have far-reaching impacts. These dynamics are influenced by various factors, including monetary and fiscal policies, the impact of the COVID-19 pandemic, geopolitical conflicts, and changes in commodity prices. The impact of this instability can be seen in financial markets, macroeconomics, business and industrial sectors, and has significant socio-economic consequences. This research aims to analyze the causes, impacts, and policy responses to economic instability and global market fluctuations in 2023. The method used is a descriptive qualitative approach with data obtained from various relevant research results or previous studies. Data processing is carried out carefully to ensure accurate and in-depth analysis. The results of this research show that the combination of the impact of monetary and fiscal policies, the ongoing influence of the COVID-19 pandemic, geopolitical dynamics, and changes in commodity prices have contributed to global economic instability. This impact is manifested in financial market volatility, macroeconomic disruption, as well as impacts on business and industrial sectors. Socioeconomic consequences such as increasing poverty and income inequality underscore the need for effective policy responses. The policy responses taken include monetary policy strategies, fiscal measures, structural reforms, and international cooperation.